The Golden age of brass - Voisin, Roger 1918- (Kapp KCL 9028, 1959)
Contains brass ensembles by G. Gabrieli, A. Bonelli, G. B. Buonamente, J. Adson, M. Locke, H. Purcell, J. Pezel, G. Reiche, and J. S. Bach.